Pengaruh Fee Based Income Gadai Emas Terhadap Profitabilitas Bank Syariah Mandiri Kcp Cimahi Baros - Siti Komariah; Anastasya Aqilla Susanto; Dewi Rahmi (ITB AAS INDONESIA Surakarta, 2022)
Gold pawn is one of the Islamic bank financing products that contribute to bank income in the form of fee-based income. This study aims to determine the effect of gold pawn fee-based income on the profitability of Islamic banks at PT Bank Syariah Mandiri KCP Cimahi Baros. Based on the estimation results using the regression model, it was found that the gold pawn fee-based income had a significant effect on profitability with a coefficient value of 1.260, meaning that for every 1% addition to the value of fee-based income, the profitability value increased by 1.260%.